2009
DOI: 10.1007/s00167-009-1010-y
|View full text |Cite|
|
Sign up to set email alerts
|

Rotational laxity greater in patients with contralateral anterior cruciate ligament injury than healthy volunteers

Abstract: Rotational stability of the knee has been traditionally difficult to quantify, limiting the ability of the orthopedic community to determine the potential role of rotational laxity in the etiology of anterior cruciate ligament (ACL) injuries. The purposes of this multicenter cohort study were to evaluate the reliability of a robotic axial rotation measurement system, determine whether the uninjured knees of patients that had previous contralateral ACL reconstruction demonstrated different rotational biomechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 24 publications
2
110
0
Order By: Relevance
“…As for rotational knee laxity, it has been shown that women have up to 40 % higher knee rotation compared to men [32]. This difference has been confirmed by several investigations [18,32,36,55]. It may represent one of the factors explaining the higher risk for ACL injuries in females.…”
Section: Influencing Factorsmentioning
confidence: 79%
See 3 more Smart Citations
“…As for rotational knee laxity, it has been shown that women have up to 40 % higher knee rotation compared to men [32]. This difference has been confirmed by several investigations [18,32,36,55]. It may represent one of the factors explaining the higher risk for ACL injuries in females.…”
Section: Influencing Factorsmentioning
confidence: 79%
“…Electromagnetic sensors placed on the proximal tibia showed that tibial rotation represented in average 48.7 % of the total rotation measured at the foot [36]. Inter-rater ICC for total range of rotation reached 0.97 at a torque of 5.65 Nm [36]. The average expected difference between two measurements as measured with the repeatability coefficient reached 6.9°for internal rotation and 3.5°for external rotation [37].…”
Section: Static Rotational Knee Laxitymentioning
confidence: 93%
See 2 more Smart Citations
“…35 Despite these associations, it is not yet clear whether the assessment of hip laxity would further discriminate injury potential beyond the laxity variables previously examined. To date, associations between joint laxity and ACL injury risk are largely based on sagittal-plane joint laxity (GJL, anterior knee laxity, genu recurvatum), 1-3,37-41 with 1 study accounting for transverse-plane knee laxity 42 and none accounting for rotational hip laxity. Given the growing interest in the role of hip mobility and stability as a potential ACL injury risk factor 12,16,19,20 and the associations we observed in this study, further research is warranted to determine if the assessment of hip-joint laxity would (1) increase the sensitivity of GJL in predicting injury risk potential, (2) be a stronger discriminator of injury risk potential (either alone or in combination with discrete kneelaxity measures), or (3) simply provide information redundant to that already provided by GJL and other laxity variables.…”
Section: Discussionmentioning
confidence: 99%